PEMANFAATAN ALOKASI APBD OLEH BADAN LAYANAN UMUM DAERAH JAKARTA SMART CITY DALAM PENGEMBANGAN APLIKASI JAKARTA KINI SELAMA MASA PANDEMI (STUDI KASUS TAHUN ANGGARAN 2021) - Prayogo, Radito -; Adnan, Muhammad -; Manar, Dzunuwanus Ghulam (Journal of Politic and Government Studies, 2024)
Jakarta Kini (Jaki) application was developed as a public service super application which aims to simplify the public service process from various government sectors, especially during the Covid-19 pandemic. The pandemic has resulted in an increase in the budget allocation for the DKI Jakarta Provincial Government in the technology sector, especially in this case for the Regional Public Service Agency (BLUD) Jakarta Smart City, which one of their main projects is the development of the Jakarta Kini Application (Jaki). Therefore, this research aims to analyze how the abundant allocation is utilized in developing the DKI Jakarta public service super application, the Jakarta Kini Application (Jaki). To facilitate the analysis in this research, the theory used to analyze this research is the e-government theory by the Harvard JFK School of Government, where according to this theory there are three important aspects that must be present in applying the concept of digitalization in the public sector, including support (support), capacity (capacity), and value (value), using qualitative descriptive methods with data gathering techniques through interviews and documentation to study the use of the DKI Jakarta Regional Budget Allocation (APBD) in the development of the Jakarta Kini (Jaki) Application by BLUD Jakarta Smart City. The research results show that in terms of capacity, Jakarta Smart City has strong financial and human resources quality to develop the Jaki Application. However, support from the DKI Jakarta Provincial Government in terms of bureaucracy aspect is still lacking, especially because it is too focused on KSD (Regional Strategic Activities) which are the activities that intended to fulfil the Governor and Vice Governor's Work Promise for the 2017 – 2022 Anies Baswedan – Sandiaga Uno working period and are part of the DKI Jakarta RPJMD (Regional Medium Term Development Plan) 2017 – 2022. This lack of support impact the value felt by the people of Jakarta. Even though some people feel the benefits of the Jaki Application, many do not, which can be seen in the user rating of the Jaki Application on the Google Playstore platform, which has an average rating of 3.7 out of 5 and many negative comments from users. This shows the need to increase bureaucracy support on the development of Jaki and focus on improving the app user experience so that the benefits felt by the people of Jakarta can be maximized.